2021
DOI: 10.1177/11206721211064017
|View full text |Cite
|
Sign up to set email alerts
|

Bacillary layer detachment on optical coherence tomography in exudative age-related macular degeneration

Abstract: Purpose To report the bacillary layer detachment on optical coherence tomography in exudative age-related macular degeneration. Methods Retrospective, observational cases Case descriptions Two cases of exudative age-related macular degeneration, one diagnosed as polypoidal choroidal vasculopathy following exudative age-related macular degeneration and other as wet age-related macular degeneration with choroidal neovascular membrane showed separation of myoid and ellipsoid zones of photoreceptor layer on optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…To date, only several studies have evaluated the characteristics and clinical significance of BALAD in neovascular AMD. 10,[14][15][16] The presence of BALAD in neovascular AMD was first reported by Liakopoulos et al 14 They found an accumulation of atypical outer retinal fluid between the external limiting membrane and the outer photoreceptor band in OCT. All cases demonstrated the findings only at one time point during the follow-up. In addition, this finding was not considered to preclude subsequent improvement in visual function.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…To date, only several studies have evaluated the characteristics and clinical significance of BALAD in neovascular AMD. 10,[14][15][16] The presence of BALAD in neovascular AMD was first reported by Liakopoulos et al 14 They found an accumulation of atypical outer retinal fluid between the external limiting membrane and the outer photoreceptor band in OCT. All cases demonstrated the findings only at one time point during the follow-up. In addition, this finding was not considered to preclude subsequent improvement in visual function.…”
Section: Discussionmentioning
confidence: 89%
“…To date, only a paucity of knowledge is available regarding the characteristics and clinical features of BALAD in neovascular AMD. 10,[14][15][16] To the best of our knowledge, the exact incidence of BALAD in neovascular AMD remains to be elucidated. In addition, the incidence of BALAD among the different types of MNV has not yet been directly compared in studies.…”
mentioning
confidence: 99%
“…Eyes with BALAD show improvement in visual acuity following treatment, whereas eyes with bridge arch-shaped SRF show a deterioration in the final visual acuity. 4,10,11 In our series, we noted that the SRF did not spread laterally because of the presence of fibrous adhesions between the RPE and the sensory retina as a result of subretinal fibrosis, thus leading to a sharp elevation of the neurosensory retina. Compartmentalization of SRF by fibrous septae was another unique feature noted in our series.…”
Section: Discussionmentioning
confidence: 65%
“…8,9 A recent article by Jung et al described 14 patients with Type-2 macular neovascularization with associated subretinal hemorrhage and BALAD. 10,11 In these cases, the BALAD resolved following therapy with intravitreal anti-VEGF injections. The major difference between BALAD and bridge arch–shaped SRF is that BALAD is seen in the acute CNVM stage of nAMD, whereas bridge arch–shaped SRF develops in chronic scarring stage of nAMD.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation